(untitled) (Mugda Medical College Journal, 2025)
One of the most frequent neurological emergencies in Bangladesh is stroke. Poor outcome and long-term disability may result from close relatives of stroke patients not being aware of the risk factors, symptoms, and recommended for the aftermath. A hospital-based cross-sectional, descriptive study was conducted to assess the levels of awareness among the close relatives of stroke patients regarding management of stroke. We conveniently selected 110 close relatives of stroke patients who were admitted into Dhaka Medical College Hospital, Dhaka, Bangladesh. The study was carried out between January and December of 2019. The mean age of the close relatives was 38.1±11.6 years. One-third of the participants were illiterate (24.5%) and half of the participants were homemakers (50.9%). Regarding awareness about immediate reactions in stroke patients, most of them said that they started treatment with a family physician (59.1%) and waited and observed (54.5%). Regarding awareness about the prevention of stroke, most of them reported regular checkups with their doctor and lifestyle modification (37.3%). Regarding awareness about suitable treatment options for stroke, most of them said spiritual belief (51.8%) and physiotherapy (40.0%). Nearly two-thirds of the participants (72.7%) had a poor level of awareness, and only a few had a good level of awareness (2.7%). The levels of awareness of the participants were statistically significant with their education and occupation (p<0.05). Our study revealed that there was a poor level of awareness about stroke among the participants. In both urban and rural communities, continual health education programs and interventions for the control of stroke risk factors can be implemented to raise the levels of awareness about stroke among relatives. Mugda Med Coll J. 2024; 7(2): 89-94